PERANAN GURU SOSIOLOGI DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS XI IIS DI SMAN 5 PONTIANAK - Andriani, Ayu (Jurnal Pendidikan Sosiologi dan Humaniora, 2018)
The title this research is "the role of sociology teacher in fostering learning motivation of class XI IIS students at SMAN 5 Pontianak". The pupose of this research is to understand teachers role as a motivator, director and faciliator in fostering learning motivation of class XI IIS students at SMAN 5 Pontianak. The method in this research is qualitative method with descriptive analysis. The techniques uset with obtain data in this research are observation, interview and documentation. The subjects of this research are one of the sociology teachers, Mrs uniek Prasetyaningrum and 6 students of XI IIS who have a low motivation in laerning. The result of this research shows that the role of sociology teacher are: (1) As a motivation, a teacher motivate students to study hard and gives warning to students. (2) teacher as a director has responsibility to make students discipline so they can learn well in classroom, monitoring, and controlling students behaviour so they will not break the rules in classroom. (3) teacher as facilitator has responsibility to provide facilities for students, like media in teaching learning process.